Analysis of the Intrinsic Elements of the Novel Ada Apa Dengan Aku, Kalian, dan Garis Tuhan: Changes in Children’s Behavior and a Mother’s Affection - zarinafadia zahra (Universitas Negeri Semarang, 2026)
Literary works are expressions of human thought conveyed through aesthetic language. This study analyzes the intrinsic elements of the novel Ada Apa Dengan Aku, Kalian, dan Garis Tuhan by Sri Wahyuni using a descriptive qualitative approach. The findings indicate that the novel highlights the influence of the environment on the formation of a child’s character, leading to self-awareness through a mother’s affection. The narrative is structured with a progressive plot and reinforced by elements of characterization, setting, first-person point of view, and figurative language. These intrinsic elements collectively create a harmonious narrative, with a religious family background serving as a crucial factor in character development and conflict, while conveying moral values of responsibility, honesty, and courage in self-improvement.